New coastal and insular species of the bromeligenous Scinax perpusillus group, from the State of Rio de Janeiro, Brazil (Anura, Hylidae) - Da Silva, Helio Ricardo; Silva, Ricardo Alves- (Zootaxa, 2008)
We describe a new bromeligenous species of Scinax from the perpusillus group from the Atlantic Forest of the State of Rio de Janeiro, Brazil. The new species is described from three different localities, two on the continent (Municipality of Mangaratiba), and the other on an island, Gipóia (Municipality of Angra dos Reis). The new species may be easily diagnosed from all other known species in the group by the color pattern of the tadpole, by the prominent medial process between the nostrils in adults. While in all the other species the tadpole has a uniform dark brown coloration, in the new species tadpoles is similarly dark brown, but also has a yellow stripe on the head between the nostrils and the eyes.